The Agathas - Glasgow, Kathleen, 1969-; Lawson, Liz, 1980- (Delacorte Press, 2022)
Alice Ogilvie's disappearance last summer is the biggest scandal at Castle Cove High School--until her ex-boyfriend is accused of murdering his new girlfriend, and Alice must pair up with her tutor Iris Adams to clear his name by relying on the wisdom of Agatha Christie.